2014
DOI: 10.1186/1471-2474-15-208
|View full text |Cite
|
Sign up to set email alerts
|

Association between low-frequency ultrasound and hip fractures - comparison with DXA-based BMD

Abstract: BackgroundNew methods for diagnosing osteoporosis and evaluating fracture risk are being developed. We aim to study the association between low-frequency (LF) axial transmission ultrasound and hip fracture risk in a population-based sample of older women.MethodsThe study population consisted of 490 community-dwelling women (78–82 years). Ultrasound velocity (VLF) at mid-tibia was measured in 2006 using a low-frequency scanning axial transmission device. Bone mineral density (BMD) at proximal femur measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this study reports, for the first time, the concurrent in vivo estimates of two cortical bone quality markers, Ct.Th and Ct.Po, using an US modality based on the propagation of guided waves and their association with fractures. Some earlier studies have reported on fracture discrimination with US axial transmission measurements at high (approximately 1.0 MHz) or low frequencies (approximately 250 kHz) on the radius or tibia . Unlike these earlier studies relying on the FAS velocity, the estimated QUS parameters here were not directly measured, but were derived from a model‐based inverse problem approach that was previously validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this study reports, for the first time, the concurrent in vivo estimates of two cortical bone quality markers, Ct.Th and Ct.Po, using an US modality based on the propagation of guided waves and their association with fractures. Some earlier studies have reported on fracture discrimination with US axial transmission measurements at high (approximately 1.0 MHz) or low frequencies (approximately 250 kHz) on the radius or tibia . Unlike these earlier studies relying on the FAS velocity, the estimated QUS parameters here were not directly measured, but were derived from a model‐based inverse problem approach that was previously validated.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies have reported on fracture discrimination with US axial transmission measurements at high (approximately 1.0 MHz) or low frequencies (approximately 250 kHz) on the radius or tibia. (21,22,24,(48)(49)(50) Unlike these earlier studies relying on the FAS velocity, the estimated QUS parameters here were not directly measured, but were derived from a model-based inverse problem approach that was previously validated. This procedure, applied in vivo at the one-third distal radius of healthy subjects, yielded thickness estimates in good agreement with ground truth values derived from site-matched HRpQCT measurements.…”
Section: Discussionmentioning
confidence: 99%